Prevalence and three-year follow-up of patients with isolated myocardial bridge in the mid-Black Sea region: a retrospective single-center study - Aytekin Aksakal; Mehmet Urumdaş; Mehmet Yaman; Ahmet Hakan Ateş; Uğur Arslan (KARE Publishing, 2016)
Objective: Myocardial bridge (MB), also known as muscular bridge, is a rare congenital disease with relatively good prognosis. However, it has been associated with unstable angina, myocardial infarction, and sudden cardiac death. Incidence and prognosis of patients diagnosed with isolated MB after having undergone coronary angiography are evaluated in the present retrospective study. Methods: Coronary angiograms of 18,250 patients, obtained between 2008 and 2011, were reexamined for presence of MB at the cardiology clinic. Of these patients, 241 (0.95%) had MB, and 181 (0.99%) had it as an isolated finding. Patients with isolated MB were divided into 2 groups according to severity of the lesion in the cardiac systole. Group 1 was comprised of patients with non-critical (<70%) stenosis; group 2 was comprised of patients with critical (≥70%) stenosis. Demographic characteristics, symptoms at initial diagnosis, and coronary angiographic findings regarding localization and severity of stenosis were noted. Follow-up was performed by phone, with outpatient clinic visits, and by reviewing hospital records. Results: Twenty-five patients (13%) had critical stenosis (group 2), and 146 (87%) had non-critical stenosis (group 1). Mean follow-up duration was 38+-7 months. Recurrent angina and repeated coronary angiography were reported in 15 group 1 patients (10.2%) and in 2 group 2 patients (8.0%) (p=nonsignificant). No instance of myocardial infarction was reported. Conclusion: Isolated MB seems to be a relatively benign disease, a conclusion made in accordance with those of previous studies. Symptoms and prognosis are not determined by degree of stenosis generated by the muscular bridge.